Trinidad, Seaside Carenage - (:unkn) unknown (My University, 2009)
Carenage , a small fishing village on the north western coast of Trinidad where on the shore there is a fishing net hanging on poles for repair and two small structures among the coconut trees and in the background, the mountains towering over the coast.
Colour; Black and White; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Carenage; Fishing villages; Coasts